BIOMARCADORES GENOTÓXICOS E HISTOLÓGICOS EM Ucides cordatus (CRUSTACEA, DECAPODA) INDICATIVOS DE IMPACTOS EM ÁREAS PORTUÁRIAS E DE MANGUEZAIS DA ILHA DO MARANHÃO - PROTAZIO, Gerson dos Santos (2020)
Coastal environments are strongly influenced by economic activities such as industries, ports, mining companies and untreated domestic and industrial effluent discharges that can be harmful to aquatic organisms that reside in these environments. Biomarkers are able to diagnose the health of organisms in these areas of high economic activity such as the industrial and port complex of São Luís, allowing mitigating measures in the biomonitoring of these places. This study aimed to evaluate the genotoxic and histological damage in Ucides cordatus (Linnaeus, 1763), indicative of anthropic impacts in a port and mangrove area of the Maranhão Island. Two semi-annual collections were carried out in periods of drought and rain in two mangrove areas (P1 = port region, São Luís; P2 = Rio Paciência Estuary, Raposa). Ten specimens of crabs were collected from inside their dens. For each specimen sampled, the biometric data of bag width and length (LC, DC in cm), width and length of the pack (LCQ, CPQ in cm), length of the movable finger (CDM in cm) and total weight (PT in g) were obtained. Gills and hemolymph samples from each specimen were subjected to standard histological technique and smear procedures for the micronucleus test. Parallel to the collections, the physical-chemical parameters of the water were measured. The results showed that the salinity was lower for the port region (P1) in the rainy season. Biometrics indicated that the crabs were larger and heavier for the rainy season in both areas, with a difference (p <0.05) in relation to the dry season. The correlation analyzes between the biometric parameters (PT, CC and LC) showed a difference (p <0.05) for the port region in the rainy season in relation to the length of the crustaceans. Crabs with a higher frequency of micronuclei and a greater number of branchial lesions were found in the port region. The correlation of altered biological responses (micronuclei and branchial lesions) with biometrics suggests that the adverse effects on these organisms are intensified in the rainy season that occurs in the São Luís port region.